Proteasomal chymotrypsin-like peptidase activity is required for essential functions of human monocyte-derived dendritic cells - Naujokat, Cord; Berges, Carsten; Höh, Alexandra E.; Wieczorek, Hubert; Fuchs, Dominik; Ovens, Jörg; Miltz-Savidis, Marion; Sadeghi, Mahmoud; Opelz, Gerhard; Daniel, Volker (Immunology, 2007)
The ubiquitin-proteasome pathway is the principal system for extralysosomal protein degradation in eukaryotic cells, and is essential for the regulation and maintenance of basic cellular processes, including differentiation, proliferation, cell cycling, gene transcription and apoptosis. The 26S proteasome, a large multicatalytic protease complex, constitutes the system's proteolytic core machinery that exhibits different proteolytic activities residing in defined proteasomal subunits. We have identified proteasome inhibitors - bortezomib, epoxomicin and lactacystin - which selectively inhibit the proteasomal β5 subunit-located chymotrypsin-like peptidase activity in human monocyte-derived dendritic cells (DCs). Inhibition of proteasomal chymotrypsin-like peptidase activity in immature and mature DCs impairs the cell-surface expression of CD40, CD86, CD80, human leucocyte antigen (HLA)-DR, CD206 and CD209, induces apoptosis, and impairs maturation of DCs, as demonstrated by decreased cell-surface expression of CD83 and lack of nuclear translocation of RelA and RelB. Inhibition of chymotrypsin-like peptidase activity abrogates macropinocytosis and receptor-mediated endocytosis of macromolecular antigens in immature DCs, and inhibits the synthesis of interleukin (IL)-12p70 and IL-12p40 in mature DCs. As a functional consequence, DCs fail to stimulate allogeneic CD4+ and CD8+ T cells and autologous CD4+ T cells sufficiently in response to inhibition of chymotrypsin-like peptidase activity. Thus, proteasomal chymotrypsin-like peptidase activity is required for essential functions of human DCs, and inhibition of proteasomal chymotrypsin-like peptidase activity by selective inhibitors, or by targeting β5 subunit expression, may provide a novel therapeutic strategy for suppression of deregulated and unwanted immune responses.
Gesehen am 19.02.2021